The Development of Academic Administration Model to Enhance Professional Skills and Experience of Suratthani 2 School Cluster Under the Secondary Educational Service Area Office Suratthani Chumphon - Jitsue, Jutharat; Boonchit, Yanisa; Pechrpuang, Sopon (Journal of Graduate MCU KhonKaen Campus, 2022)
The objectives of this study were: 1) to study the state and guidelines of academic administration to enhance professional skills and experience; 2) to develop the academic administration model to enhance professional skills and experience; and 3) to assess the suitability and feasibility of the academic administration model to enhance professional skills and experience of schools in Suratthani 2 School Cluster under The Secondary Educational Service Area Office Suratthani Chumphon. The research procedure consisted of Fifty-one key informants included school administrators, teachers, and school board members, which were selected by purposively sampling. Data were collected by the questionnaire with the reliability of 0.80 and were analyzed by mean and standard deviation. In addition, this step was also used to develop the academic administration model to enhance professional skills and experience, which item congruence index was evaluated by 12 experts, used to assess the suitability and feasibility of the academic administration model to enhance professional skills and experience. The group of 51 users included school administrations, teachers, and school board members, which was selected by purposive sampling. Data were collected by the questionnaire with the reliability of 0.78 and were analyzed by mean and standard deviation. The research findings were as follows. 1) The state of the academic administration was in a high level in two aspects including curriculum development and learning administration; moreover, evaluation was in a moderate level. The desirable state of the academic administration was in the highest level; furthermore, curriculum development was in a high level. 2) The development of the academic administration model consisted of four components: (1) Principles; (2) Objectives; (3) System and Mechanism; and (4) Terms of Use. 3) The assessment of the academic administration model showed that the suitability and feasibility of the model were in the highest level.